Colonial archaeology in South Asia the legacy of Sir Mortimer Wheeler - Himanshu Prabha Ray (Oxford University Press, 2008)
On the development of archaeology as a discipline in India during the tenure of Mortimer Wheeler, former director-general, Archaeological Survey of India.